Analysis of Solar Power Plant Planning for Lighting Dragon Fruit Orchards in Silimakuta Village, Pakpak Bharat - Alfonsus Sinamo; Muhammad Erpandi Dalimunthe; Haris Gunawan (INFOKUM, 2025)
The use of electrical energy as a lighting source in dragon fruit orchards in remote areas such as Silimakuta Village often faces challenges due to limited access to electricity from the state electricity company (PLN). Therefore, efficient and sustainable alternative energy sources are needed, one of which is through Solar Power Plants (PLTS). This study aims to calculate the power requirements and capacity of the PLTS system required to meet lighting needs in dragon fruit orchards. The research problem formulation includes how to calculate the power requirements of a PLTS system and the required power capacity. The problem definition focuses on calculating the power requirements of each component and the amount of power generated by the system to determine the number of solar modules. The research method used was to calculate the power consumption of lighting lamps, system efficiency, and the potential solar irradiation in the area. The results show that a PLTS system with a certain capacity can optimally meet nighttime lighting needs. This research provides benefits in the form of appropriate PLTS system planning, battery capacity calculations, and the utilization of renewable energy to support sustainable lighting systems in the agricultural sector.